Reconstruction from boundary measurements for less regular conductivities. (5th October 2016) - García, Andoni; Zhang, Guo
Abstract: In this paper, following Nachman's idea (1988 Ann. Math. 128 531–76 ) and Haberman and Tataru's idea (2013 Duke Math. J. 162 497–516 ), we reconstruct C 1 conductivity γ or Lipchitz conductivity γ with small enough value of ∣ ∇ log γ ∣ in a Lipschitz domain Ω from the Dirichlet-to-Neumann map Λ γ . In the1 the authors and Brown recover the gradient of a C 1 -conductivity at the boundary of a Lipschitz domain from the Dirichlet-to-Neumann map Λ γ .